Pharmacotherapy efficacy and safety criteria based on spectral shifts in elder patients with arterial hypertension and coronary artery disease - Shtanko, V. A.; Tofan, N. V.; Khyzhnyak, O. V.; Yablonska, V. B.; Novikov, S. A. (Journal of Education, Health and Sport, 2017)
The article is dedicated to development of homeostatic criteria of efficacy and safety of drugs combinations “lisinopril, bisoprolol, indapamide, isosorbide dinitrate, acetylsalicylic acid”. These criteria are based on study of homeostatic shifts and their association with clinical and laboratory parameters on elder patients with arterial hypertension (AH) II, III stage combined with coronary artery disease (CAD). Complex clinical, biochemical, biophysical and instrumental investigation was performed in 67 patients with AH II, III stage combined with CAD. On the grounds of developed criteria was established that for patients with AH II and CAD is not recommended combination “lisinopril, acetylsalicylic acid” and for those ones with AH III and CAD prohibited combinations “lisinopril, bisoprolol, acetylsalicylic acid” and “lisinopril, bisoprolol, indapamide, isosorbide dinitrate, acetylsalicylic acid” in order to prevent development of drug induced renal dysfunction. It was also determined safety of combinations “lisinopril, bisoprolol, acetylsalicylic acid”; “lisinopril, bisoprolol, indapamide, acetylsalicylic acid” for patients with AH II and CAD and “lisinopril, bisoprolol, indapamide, acetylsalicylic acid” for those ones with AH III and CAD.